Enhanced recovery of phosphate as a value-added product from wastewater by using lanthanum modified carbon-fiber. (October 2021) - Quyen, Vu Thi; Jitae, Kim; Dalahmeh, Sahar S.; Pham, Thi-Huong; Thanh, Dang My; Le, Cong Lap; Thang, Phan Quang; Viet, Nguyen Minh; Van Thuan, Doan; Nguyen, Thanh Luan
Abstract: The aim of this study is to present the potential of activated carbon fiber (CF) impregnated with lanthanum (La) as a novel adsorbent (La-CF) of phosphate-phosphorus (P) and to assess the value-added due to P-recovery from wastewater using La-CF. The CF were loaded with La and the loaded CF was then calcined at 500 °C. The La-CF adsorbent was used in a series of batch experiments to characterize the adsorption of P at pH of 6–10 and P concentrations of 1–200 mg/L. Physical-chemical properties such as surface morphology, surface charge, surface area, and surface chemistry were determined for the La-CF. The La-CF exhibited adsorption capacity of 196.5 mg/g, fast sorption kinetics and high selectivity for P removal from aqueous solution. La-CF removed 97.3% of P from wastewater and achieved P-level to below 2 mg/L. It was repetitively reused over 10 times in successive cycles to remove P from wastewater. The value-added by recovery of P from wastewater was calculated at around 0.12 US$/L, demonstrating economic benefits of La-CF. In conclusion, the successful removal, recycling, and recovery value-added of P using La-CF adsorbent displayed good potential for developing the technology for treatment of wastewaters to recover valuable compounds such as phosphorus. Graphical abstract: Image 1 Highlights: La-CF displayed as low-cost adsorbent for removal and recovery of P from wastewater. La-CF repetitively reused over 10 cycles with high P removal efficiency. Value-added from P recovery in secondary wastewater was 0.12 US$/L.